Pengaruh Aplikasi Nutri DASH dalam Konseling Gizi terhadap Pengetahuan, Aktivitas Fisik, Asupan Natrium dan Serat Pasien Hipertensi di Puskesmas Gamping II - Sari, Tjarono; Dita Nareswari, Irene; Anggoro, Sarni (Universitas Widya Mataram, 2025)
Hypertension or high blood pressure disease is a chronic condition characterized by an increase in blood pressure of more than 140/90 mmHg. Complications of hypertension caused by high mortality Dietary management in hypertensive patients should be a serious concern. Dietary management for hypertension patients is carried out with the DASH Diet (Dietary Approach to Stop Hypertension) which is a diet of vegetables and fruits that contains a lot of dietary fiber and minerals and the salt intake is limited. The purpose of this study is to determine the difference in the use of the Nutri-DASH application in nutritional counseling to knowledge, physical activity, sodium and fiber intake of hypertension patients at the Gamping II Health Center. This research method uses a quasi-experimental type. The sampling technique was carried out by purposive sampling of 30 people. The data collected included pretest knowledge, physical activity, sodium intake, fiber intake.